Rereading the Impressions of Violence on Women's Identity and Mental Health- A Literary Analysis through the Works of Manjula Padmanabhan, Poile Sengupta, and Kishwar Desai (Journal of Namibian Studies : History Politics Culture, 2023)
The research paper aims to explore the effects of violence on women's identity and mental health through a literary analysis of the works of Manjula Padmanabhan, Poile Sengupta, and Kishwar Desai. The purpose of this research is to investigate how these well-known female authors portray the effects of violence on the lives, sense of self, and psychological well-being of women in their written works. This study intends to contribute to a fuller understanding of the complicated relationship between violence, gender, and mental health by analyzing the authors' previous studies. In doing so, the authors hope to shed light on the particular difficulties women confront in societies plagued by violence. The results of this research have the potential to provide policymakers, mental health practitioners, and social advocates with information that can inform the development of tailored interventions to support women who have been harmed by violence.